Development of a remotely controllable 4 m long aerial-hose-type firefighting robot - Yamauchi, Yu; Maezawa, Yukihiro; Ambe, Yuichi; Konyo, Masashi; Tadakuma, Kenjiro; Tadokoro, Satoshi (Frontiers in Robotics and AI, 2023)
In a fire outbreak, firefighters are expected to rapidly extinguish fires to stop the spread of damage and prevent secondary disasters. We proposed the concept of a dragon firefighter (DFF), which is a flying-hose-type firefighting robot. We developed a 3.6 m long DFF equipped with two nozzle units and achieved stable flight. However, the system was not yet completed because the root of the robot, which should have been operated remotely, was operated manually. In addition, the system’s reliability was insufficient to successfully repeat the demonstration several times. The development of a robot demonstration system is crucial for the practical application of such a firefighting robot. In this study, we developed a demonstration system for a remotely controllable 4 m flying firehose robot for demonstration at the World Robot Summit 2020 (WRS 2020) opening ceremony in Fukushima as a milestone. This paper focuses on the following issues: 1): installation of the remotely controllable mobile base, 2): redesign of the water channels (the sizes of nozzle outlets) to get enough thrusts to fly with a fire engine, 3): development of nozzle units with a larger movable range (1.5 times larger than the conventional nozzle) in addition to waterproofing technique to improve system reliability, and 4): redesign of a passive damping mechanism to ensure better stability. Thus, a firefighting demonstration was successfully conducted at the opening ceremony of the World Robot Summit 2020 in Fukushima, Japan, and we discuss the lessons learned through the demonstration. We found that the developed DFF system incorporating a mobile base could achieve remote fire extinguishing.